Using the Geology of Your Neighbourhood and City for Geoscience Outreach - Edwards, W.A. (Geoscience Canada, 2009)
SUMMARY Most Canadians live, work and attend school in urban areas. Your neighbour-hood has wonders such as snow-bank stratigraphy, sidewalk sedimentology, and building stone. Urban fieldtrips require little money and little time to run and they can inspire participants. An inner-city school teacher confirmed my belief in urban fieldtrips when she said, “I’ve never been able to take my students anywhere but we can now take a city bus downtown and see the world. Thank You!” So open your eyes to the grand world of geology around you. Take others on a neighbourhood trip; you will inspire, motivate and educate them.